An evaluation of advance care planning during the COVID-19 pandemic: a retrospective review of patient involvement in decision making using routinely collected data from digital ReSPECT records. Issue 4 (2021) - Hurlow, Adam; Wyld, Lucy; Breen, Andrew
No abstract available